Effects of dynamic vulcanization on thermal properties of calcium carbonate filled polypropylene/ethylene propylene diene terpolymer composites - Siti Rohana, Ahmad; Salmah, Husseinsyah, Prof. Madya Dr. Ir.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Putra Malaysia Press, 2012)
Link to publisher homepage at http://www.pertanika.upm.edu.my